Spontaneous rectus sheath hematoma mimicking acute abdomen (Indian Journal of Case Reports, 2018)
Rectus sheath hematoma has been described in the past due to various etiologies with varying degrees of severity. It is a rare cause of acute abdomen. Clinical presentation may vary from person to person and based on site of collection and source of bleeding. Various management options including surgical and non-surgical measures have been described and generally present with tenderness with a mass of varying size based on the duration and amount of bleeding. Here, we present the case of a 72-year-old female with acute abdomen on presentation, unstable vitals, and severe pallor. A tender mass over the left lower part of the abdomen was found, and on further evaluation with imaging, the patient was found to have a rectus sheath hematoma. The hematoma was successfully treated with the evacuation of the hematoma and ligation of the bleeding vessel.